Pengaruh Fungsi Pengawasan Internal dan Eksternal Perusahaan, dan Financial distress terhadap Manajemen Laba - Ocha Rosyanna; Fitrini Mansur; Gandy Wahyu Maulana Zulma (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Delegation of management authority from owners to management within the company creates agency problems. With the separation between ownership and management of the company will bring up differences in interests between agents and principals. The management (agent) takes advantage of information asymmetry by modifying earnings information to achieve the company's goal of increasing profits. This study aims to test empirically regarding the effect of internal and external control of the company, and financial distress on earnings management. The population and sample in this study are property & real estate companies listed on the Indonesian stock exchange which were selected using the purposive sampling method, so that a total of 200 samples were obtained for the 2017-2021 period. Data analysis techniques in this study were descriptive statistical tests and PLS-SEM tests which included outer model tests and inner model tests. The results of hypothesis testing show that the company's external control and financial distress have an effect on earnings management, while the company's internal control has no effect on earnings management. The limitations of this research are that the companies that are the sample in this study only focus on companies in the property and real estate sector, and many companies do not publish their complete annual reports from 2017-2021.